Influence of mesh sizes and orientations on expanded aluminium sheets on tensile performances - Nik Ismail, N A; Roslan, M N; Ismail, A E; El Bakri, H M (2022)
Nowadays, the demand of usage for aluminium mesh has increased in many types of applications. As a result of this trend, studies on the mesh conditions of these materials are becoming increasingly important. Based on this information, this study investigates the effect of mesh sizes and orientation of Aluminium expanded mesh sheets on their tensile properties. The experiment is carried out by using three types of Aluminium expanded mesh sheets with different mesh sizes: fine mesh (2.0 x 3.5mm), medium mesh (3.0 x 4.0mm) and coarse mesh (8.0 x 12.0mm). There are two types of mesh orientation involved for each mesh size: the original orientation (30°) and its rotated orientation (60°). According to the results of the experiment, specimens with fine mesh have higher tensile stress, which is 44.90 MPa for fine mesh specimens with a 30° orientation, compared to medium and coarse mesh sizes, which have the lowest strength, which is 7.06 MPa for coarse mesh specimens with a 60° orientation. In terms of orientation, the specimens with 60° orientation have smaller tensile stress than those with 30° orientation. However, the strain values were higher for specimens with 60° orientation than specimens with 30° orientation